In situ synthesis of a Fe3S4/MIL-53(Fe) hybrid catalyst for an efficient electrocatalytic hydrogen evolution reaction. Issue 31 (1st April 2019) - Huang, Dan-Dan; Li, Shuang; Wu, Ya-Pan; Wei, Jun-Hua; Yi, Jing-Wei; Ma, Hai-Meng; Zhang, Qi-Chun; Liu, Yun-Ling; Li, Dong-Sheng
Abstract : By modulating the Fe3 S4 /MIL-53(Fe) ratio with a controlled partial sulfurization strategy, the Fe3 S4 (52.1 wt%)/MIL-53 hybrid catalyst with an ideal hierarchical nanostructure and composition exhibited high HER activity. Abstract : The development of efficient MOF-based electrocatalysts with good stability to produce hydrogen is a great challenge in the field of sustainable energy conversion. Herein, we introduced a controlled in-situ sulfurization strategy to generate a highly active and stable hybrid catalyst containing good conductive Fe3 S4 ultrasmall nanosheets attached on the surface of 3D MIL-53(Fe) for the hydrogen evolution reaction in acidic solutions.